School leadership and its impact on student achievement: The mediating role of school climate and teacher job satisfaction. Issue 6 (8th August 2016) - Dutta, Vartika; Sahney, Sangeeta
Abstract : Purpose: The present study examines the role of teacher job satisfaction and school climate in mediating the relative effects of principals' instructional and transformational leadership practices on student outcomes. Design/methodology/approach: Guided by strong evidence from theories on school leadership and work psychology, we hypothesized relations among dimensions of principals' instructional and transformational leadership behaviors, teachers' perception of the school climate (social and affective, and physical environment), their job satisfaction, and student achievement. The benefits of the principal's leadership behaviors for student achievement are primarily hypothesized as indirect, with either a weak or statistically non-significant direct positive effect on student outcomes. Path modeling was applied to validate a mediated-effects model using cross-sectional survey data (306 principals, 1539 teachers) obtained from 306 secondary schools in the two Indian metropolitan cities of New Delhi and Kolkata. Findings: Principal leadership behaviors were not associated directly with either teacher job satisfaction or school-aggregated student achievement. Rather, the transformational leader behavior showed an indirect effect, through the social and affective component of the school climate, on teacher job satisfaction. The physical climate however appeared to play a dominating role in mediating the instructional leadership effects on teacher job satisfaction. Comparing the relative indirect effect sizes of the instructional and transformational leadership behaviors on student achievement, principals appear to favour the former approach. Originality/value: This study provides further empirical evidence that instructional leadership better captures the impact of school leadership on student outcomes, when compared to its transformational counterpart. By identifying the relative effects of different leadership practices, school leaders and educational practitioners can focus more on altering the distribution and frequency of those practices that work best for ameliorating student achievement levels.